Perception the art of seeing - McIntyre, Flora; Stage Fright Productions; Learning Seed Company (Lake Zurich, IL: The Learning Seed, 1997)
Looks at the difference between how one perceives things and how one sees things
With Flora McIntyre
Keywords: Perception